2022
DOI: 10.2147/cmar.s362666
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Management of Dysphagia in Patients with Inoperable Esophageal Cancer: Current Perspectives

Abstract: The majority of patients with esophageal cancer are diagnosed at an advanced, incurable stage. Palliation of symptoms, specifically dysphagia, is a crucial component to improve quality of life and optimize nutritional status. Despite multiple available treatment modalities, there is not one accepted or recommended to be the preferred treatment option. Palliative management is often decided by a multidisciplinary team considering factors including local availability, preference, patient life expectancy, and sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Dysphagia is one of the most debilitating symptoms of advanced esophageal cancer and can often be challenging to manage [7]. Partially covered and fully covered selfexpanding metal stents are the most preferred modality for palliating symptomatic dysphagia in inoperable esophageal cancer [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysphagia is one of the most debilitating symptoms of advanced esophageal cancer and can often be challenging to manage [7]. Partially covered and fully covered selfexpanding metal stents are the most preferred modality for palliating symptomatic dysphagia in inoperable esophageal cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, the choice is often based on availability or endoscopist's preference and experience. Systemic chemotherapy can improve dysphagia, but this typically happens at a slow pace and can often be incomplete, resulting in the need for alternate intervention [7]. A Cochrane systematic review concluded that systemic therapy improves dysphagia but recommended against using chemotherapy alone in dysphagia palliation for esophageal cancer due to high incidence of recurrence and unclear impact on quality of life [26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[1,2] Palliation of malignant dysphagia represents the most common indication for ES, as esophageal cancer is mainly diagnosed in advanced stages in the majority of patients. [3,4] Post-operative leaks, fistulas, or perforations can be treated endoscopically with ES, thus offering a minimally invasive and low-morbidity choice. Additionally, in selected cases with benign strictures ES could be an option and in patients with acute variceal bleeding and failed ligation, stent placement could offer a life-saving solution, by providing a time window for further interventions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Apostolis Papaefthymiou MD 1 , Paraskevas Gkolfakis MD 2,3 , Kirill Basiliya PhD 1 , Daryl Ramai MD 4 , Georgios Tziatzios PhD 2 , Vinay Sehgal MD 1 , Andrea Telese MD 1 , Benjamin Norton MD 1 , Nasar Aslam MD 1 , Gavin Johnson MD 1 , Rehan Haidry PhD 1,5 This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation